Strategi Intelijen Kejaksaan Tinggi Bali dalam Mengamankan Pelaksanaan Pilkada Serentak 2024 - Sonia, Nafira Nindya Ayu; Wirantari, I Dewa Ayu Putri (Lenggogeni Data Publishing, 2025)
The 2024 Simultaneous Regional Head Elections present a major challenge for the Bali High Prosecutor’s Office in maintaining socio-political stability and regional security. Through the Intelligence Division, the Prosecutor’s Office has an important role in early detection of potential disturbances, preventing conflict, and ensuring that the regional head election process takes place democratically. This study aims to analyze the security strategy implemented by the Bali High Prosecutor’s Office, with an emphasis on aspects of supervision, cross-agency coordination, and the use of information technology. The research method used is a descriptive qualitative approach through interviews, participatory observation, and documentation during internship activities. The results of the study indicate that the strategies implemented are preventive and collaborative, including the establishment of election posts, the use of the Inteliz Pro application, digital space supervision, and public education through programs such as “Jaksa Menyapa”. However, challenges such as money politics, limited personnel, and the influence of non-local residents and foreign nationals in the public space need to be addressed more seriously. This study recommends strengthening cross-agency coordination, verifying non-local voter data, and increasing the capacity of intelligence human resources to support a safe and conducive regional head election. ABSTRAK Pemilihan Kepala Daerah (Pilkada) Serentak 2024 menghadirkan tantangan besar bagi Kejaksaan Tinggi Bali dalam menjaga stabilitas sosial-politik dan keamanan daerah. Melalui Bidang Intelijen, Kejaksaan memiliki peran penting dalam mendeteksi dini potensi gangguan, mencegah konflik, serta memastikan proses Pilkada berlangsung secara demokratis. Penelitian ini bertujuan untuk menganalisis strategi pengamanan yang diterapkan Kejaksaan Tinggi Bali, dengan menitikberatkan pada aspek pengawasan, koordinasi lintas lembaga, serta pemanfaatan teknologi informasi. Metode penelitian yang digunakan adalah pendekatan kualitatif deskriptif melalui wawancara, observasi partisipatif, dan dokumentasi selama kegiatan magang. Hasil penelitian menunjukkan bahwa strategi yang diterapkan bersifat preventif dan kolaboratif, mencakup pembentukan posko pemilu, penggunaan aplikasi Inteliz Pro, pengawasan ruang digital, serta edukasi publik melalui program seperti “Jaksa Menyapa”. Namun, tantangan seperti politik uang, keterbatasan personel, dan pengaruh warga nonlokal maupun WNA dalam ruang publik perlu ditangani lebih serius. Penelitian ini merekomendasikan penguatan koordinasi lintas lembaga, verifikasi data pemilih nonlokal, serta peningkatan kapasitas SDM intelijen guna mendukung Pilkada yang aman dan kondusif. Kata kunci: Strategi Intelijen, Kejaksaan Tinggi, Pilkada 2024.